Thermoelectric power sources using low-grade heat : Part 2 - Anatychuk, L.I.; Prybyla, A.V.; Korop, M.M.; Kiziuk, Yu.V.; Konstantynovych, I.A. (Journal of Thermoelectricity, 2024)
This work is the second part of a series of studies on thermoelectric power sources using low-grade heat. The results of computer-aided design of a thermoelectric generator with forced convection heat exchange that uses thermal waste from industrial installations are presented. The generator design has been developed and a series of experimental studies have been conducted on a test bench. Bibl. 9, Figs. 5.